Fully alternating and regioselective ring-opening copolymerization of phthalic anhydride with epoxides using highly active metal-free Lewis pairs as a catalyst. Issue 29 (16th July 2018) - Kummari, Anjaneyulu; Pappuru, Sreenath; Chakraborty, Debashis
Abstract : Cooperative metal-free Lewis pairs effectively catalysed controlled ring-opening copolymerization of phthalic anhydride (PA) with epoxides. Abstract : A recent study has been directed to the design of metal-free Lewis pair catalysts for ring-opening alternating copolymerization (ROAP) reactions to enhance both activity and selectivity. While the simplest types of organic bases/Lewis bases (for example: PPN + Cl −, DMAP, DBU and TBD) are able to copolymerize anhydride-epoxide in a non-living and non-quantitative manner, the introduction of Lewis acids radically changes this behaviour. In this study, various Lewis acids such as B(C2 H5 )3, Al(CH)3, Et2 Zn and n Bu2 Mg in combination with various Lewis bases such as PPN + Cl −, DMAP, DBU and TBD were tested as Lewis pair catalysts for anhydride-epoxide ring-opening copolymerization (ROCOP) studies. Based on the observed results, the B(C2 H5 )3 /PPNCl pair stood out as the most active and effective Lewis pair for the perfectly alternating and regioselective controlled ROCOP of various epoxides (cyclohexene oxide, CHO; tert -butyl glycidyl ether, t BGE and 2-benzyloxirane, BO) with phthalic anhydride (PA). Medium to high molecular weight linear poly(anhydride- co -epoxide)s ( M n up to 57.5 kg mol −1 ) are achieved, and most of them exhibit narrow molecular weight distributions ( M w / M n as low as 1.07). However, in the presence of strong Lewis acids (Al(CH)3, Et2 Zn and n Bu2 Mg) and neutral Lewis bases (DMAP/DBU/TBD) this broad applicability is offset by the lack of control over the polymerizations, including the side reactions as a consequence of strong acidity/alkalinity. Hence, the ideally suitable acidity/alkalinity and matched size of the Lewis pair are considered crucial for the effective copolymerization of PA and epoxides. In addition, from P(PA- alt-t BGE) copolymers, hydroxyl-functionalized poly(ester- alt -glycerol)s were successfully synthesized by deprotection of the t -butyl groups.